Analysis of Mathematical Connection Ability Based on Student Characteristics Thinking on Discovery Learning Scientific Approach - Hidayati, Farida; Kartono, Kartono; Masrukan, Masrukan (Unnes Journal of Mathematics Education Research, 2018)
Student’s mathematical connections ability at SMK Syubbanul Wathon Tegalrejo Magelang is still low. Students are not able to relate concepts in, link the mathematical concepts to other subjects, and to problems in daily life. The study aims to describe the process of discovery learning model with scientific approach, find out the effectiveness of discovery learning of scientific approach to the student’s mathematical connection ability, and to describe the mathematical connection ability of XII graders of SMK Syubbanul Wathon on differential functions based on the characteristics of student’s way of thinking. This study used mixed method of concurrent embedded design. The sample was chosen by random sampling, XII-G3 (control class, XII-G4 (experiment class 1), and XII-G6 (experiment class 2) as quantitative data sources. Meanwhile, for the source of qualitative data, it was obtained by taking two CS students, two AS students, two CR students, two AR students. The result of the research shows that (1) the discovery learning scientific approach process in improving the students’ mathematical connection ability is good, (2) the discovery learning model with the scientific approach is effective, and (3)The characteristics student’s way of thinking also affects the students' mathematical connections ability.